Prenatal Pesticide Exposure and Maternal-Fetal Health Outcomes: A Systematic Review Informing Agro-Nursing Practice - Kurniyawan, Enggal Hadi; Afandi, Alfid Tri; Nur, Kholid Rosyidi Muhammad; Kurniawan, Dicky Endrian; Emerson, Iraha; Aung, Sa Sa (KHD Production, 2026)
Prenatal pesticide exposure poses significant risks to maternal and child health in agricultural communities worldwide. This systematic review evaluated recent empirical evidence on the impact of agricultural chemical exposure during pregnancy to inform agro-nursing practice directly. A systematic literature search was conducted in Scopus, PubMed, and ProQuest following PRISMA guidelines. Studies published within the last year, written in English, and featuring active DOIs were strictly included. Methodological quality was rigorously assessed using the Joanna Briggs Institute critical appraisal tools. Ten studies ultimately met the inclusion criteria, comprising seven cohort studies, one case-control study, one cross-sectional study, and one ecological analysis. Eight studies demonstrated high methodological quality. The synthesized evidence revealed strong associations between prenatal pesticide exposure and a range of adverse health outcomes. Specifically, exposure to organochlorines and organophosphates correlated with impaired early childhood neurodevelopment and increased childhood neuroblastoma risk. Maternal exposure to pyrethroids and organophosphates significantly elevated the risk of gestational diabetes mellitus and disrupted maternal thyroid homeostasis. Spatial analyses further confirmed increased risks of low birth weight in high-application agricultural zones. Agricultural chemical exposure during pregnancy constitutes a critical determinant of adverse perinatal outcomes. Agro-nurses must integrate comprehensive histories of environmental exposures into standard prenatal assessments. Proactive patient education and targeted clinical surveillance are essential for mitigating toxicological risks and optimizing maternal-fetal health trajectories globally